2017
DOI: 10.1016/j.annepidem.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy weight change and adverse maternal outcomes: a retrospective cohort study

Abstract: Purpose Examine associations between interpregnancy BMI change and gestational diabetes mellitus (GDM), pre-eclampsia (PE), gestational hypertension (GHtn), primary cesarean delivery, and vaginal birth after cesarean delivery (VBAC). Methods Modified Poisson regression models estimated adjusted associations. Results Every one unit increase in interpregnancy BMI increased risks of GDM (RR: 1.09, 95%CI: 1.07–1.11), PE (RR: 1.06, 95%CI: 1.04–1.09), GHtn (RR: 1.08, 95%CI: 1.06–1.10), and primary cesarean deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 39 publications
2
28
1
Order By: Relevance
“…17,21 In addition, we found that interpregnancy weight gain of >2 to 4 and >4 BMI units was associated with increasingly elevated risk of cesarean delivery, results that are consistent with previous studies among unselected populations. 19,29,43,44 Unlike Wallace et al who separately examined emergency cesarean delivery, 45 but similar to Lynes et al who did not differentiate between the different types of cesarean delivery, 19 we found similar magnitude of risk regardless of BMI in the first pregnancy. Observed association between interpregnancy weight gain and cesarean delivery may be mediated by LGA, fetal dystocia, or fetal distress, which are associated with interpregnancy weight gain and may constitute indications for a cesarean delivery.…”
Section: Comment Principal Findingssupporting
confidence: 76%
“…17,21 In addition, we found that interpregnancy weight gain of >2 to 4 and >4 BMI units was associated with increasingly elevated risk of cesarean delivery, results that are consistent with previous studies among unselected populations. 19,29,43,44 Unlike Wallace et al who separately examined emergency cesarean delivery, 45 but similar to Lynes et al who did not differentiate between the different types of cesarean delivery, 19 we found similar magnitude of risk regardless of BMI in the first pregnancy. Observed association between interpregnancy weight gain and cesarean delivery may be mediated by LGA, fetal dystocia, or fetal distress, which are associated with interpregnancy weight gain and may constitute indications for a cesarean delivery.…”
Section: Comment Principal Findingssupporting
confidence: 76%
“…Eleven studies assessed GDM, of which five studies were eligible for the meta‐analysis. The meta‐analysis found a significant, positive association between interpregnancy BMI gain and GDM development during the second pregnancy (Figure S1: OR 1.64 [95%CI 1.28‐2.11]; I 2 = 78% for BMI gain of 1 to 3 kg/m 2 ; OR 2.42 [1.62‐3.62]; I 2 = 89% for BMI gain of ≥3 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In six studies, GH was assessed . Four studies were included in the meta‐analysis, which resulted in a nonsignificant effect for BMI loss of ≥1 kg/m 2 (Figure S2: OR 1.07 [0.85‐1.34]; I 2 = 42%) on the development of GH. Increasing interpregnancy BMI gain was associated with a significantly increased risk of GH development (Figure S2: OR 1.49 [1.34‐1.66]; I 2 = 0% for BMI gain of 1 to 3 kg/m 2 ; OR 1.98 [1.56‐2.50]; I 2 = 62% for BMI gain of ≥3 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations